Technology impacts on area, production and productivity of cashew in Dakshina Kannada district, Karnataka - Sajeev, M.V.; Saroj, P.L.; Lakshmisha, R. (Journal of Plantation Crops, 2014)
The study analyses the technology impacts on area, production and productivity of cashew in the Dakshina Kannada district of Karnataka state, for combating low productivity and profitability from cashew cultivation. Results revealed that highest area under cashew is occupied by the variety Ullal-3 followed by Bhaskara with similar trend in adoption levels. The ‘Ullal-3 + Bhaskara’ combination emerged to be the most popular one among farmers in the study area. Farmers realized highest yield from cashew varieties such as Bhaskara and Madakkathara-2 followed by Ullal-1 and Ullal-3. Productivity under normal density (8 x 8 m) as well as high density (5 x 5 m) planting was highest for Bhaskara and Madakkathara-2. Correlation analysis showed that four technologies; soil and water conservation, pruning and training, plant protection and harvesting and post-harvest technologies had highly significant relation with the cashew production achieved by farmers. Increased adoption of soil and water conservation techniques, development and popularization of user friendly plant protection measures and adoption of viable intercrops can contribute largely to increase cashew production while increased adoption of pruning and training in cashew orchards can significantly increase the per unit productivity of cashew orchards. The study concludes that socio-economic and bio-physical factors along with policy environment have a larger contribution in explaining cashew production and productivity and technology component alone cannot be expected to bring a positive impact. Understanding the above dynamics in technology impact can help researchers and extension agencies working in cashew sector to design better innovations and effective outreach strategies.